SISI PARADOKS DALAM PROSES MANAJEMEN PEMILU LEGISLATIF TAHUN 2019 - Foeh, Yaherlof; Pradana, I Putu Yoga Bumi; Pah, Theny I.B Kurniati; Oktavianto, Aspri Budi; Pandie, Ardi Yosafat (Universitas Riau Kepulauan, 2024)
Abstract : This research analyzes the management of election organization and paradoxes in Indonesia's 2019 Legislative General Election. This research used a qualitative approach, interviewed 15 informants, and revealed several significant paradoxes. First, the paradox in constitutional authority between the General Election Commission (KPU) and Bawaslu, where Law No. 7 of 2017 resulted in the shallowing and weakening of the KPU's constitutional status. Second is the paradox in campaign management, which includes transactional and money politics. Third is the paradox in managing women's representation, where women are often used as tools to collect votes for male candidates. Finally, there are paradoxes in the voting process, including the increasing capitalization of votes and money politics. This research critically contributes to providing important insights into the dynamics of legislative elections in Indonesia. Keywords : paradox; constitutional; campaign; women's representation; voting. Abstrak : Pemilihan Umum Legislatif Tahun 2019 di Indonesia. Penelitian ini menggunakan pendekatan kualitatif dan mewawancarai 15 informan dan berhasil mengungkapkan beberapa paradoks signifikan. Pertama, paradoks dalam kewenangan konstitusional antara Komisi Pemilihan Umum (KPU) dan Bawaslu, di mana UU No 7 Tahun 2017 mengakibatkan pendangkalan dan pelemahan status konstitusional KPU. Kedua, paradoks dalam manajemen kampanye, yang mencakup politik transaksional dan politik uang. Ketiga, paradoks dalam manajemen keterwakilan perempuan, di mana perempuan sering dijadikan alat untuk mengumpulkan suara bagi calon laki-laki. Terakhir, paradoks dalam proses pemungutan suara, termasuk kapitalisasi suara dan politik uang yang meningkat. Penelitian ini secara kritis berkontribusi dalam memberikan wawasan penting tentang dinamika pemilihan legislatif di Indonesia. Kata Kunci : paradoks; konstitusional; kampanye; keterwakilan perempuan; pemungutan suara.